2009
DOI: 10.1007/s00701-009-0410-6
|View full text |Cite
|
Sign up to set email alerts
|

The association between high VEGF levels and multiple probable punctuate cavernous malformations

Abstract: Cerebral cavernous malformations (CCMs) are congenital abnormalities of the cerebral vessels. The de novo development of new lesions in this disease has been reported. However, the underlying mechanism of progressive CCMs in such patients remains unclear. This report documents two cases of multiple probable CCMs that showed a progressive behaviour. The plasma levels of vascular endothelial growth factor (VEGF), and transforming growth factor-beta1 (TGF-beta1) were measured using an enzyme-linked immunosorbent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 16 publications
5
10
0
Order By: Relevance
“…However, VEGF is a known regulator of pathological angiogenesis (63); thus the suggestion that VEGF/ KRIT1 cross-talk could have a function in the formation of CCM is an obvious one. Intermittent reports of increased VEGF expression in lesions or serum of CCM patients (64,65) correlate nicely with our discovery that Krit1 ϩ/Ϫ mice have higher serum levels of VEGF-A (15). However, interpretation of these clinical reports is limited by small group size and the inclusion of both sporadic and hereditary CCMs; therefore, the clinical import of VEGF signaling remains unclear.…”
Section: Discussionsupporting
confidence: 57%
“…However, VEGF is a known regulator of pathological angiogenesis (63); thus the suggestion that VEGF/ KRIT1 cross-talk could have a function in the formation of CCM is an obvious one. Intermittent reports of increased VEGF expression in lesions or serum of CCM patients (64,65) correlate nicely with our discovery that Krit1 ϩ/Ϫ mice have higher serum levels of VEGF-A (15). However, interpretation of these clinical reports is limited by small group size and the inclusion of both sporadic and hereditary CCMs; therefore, the clinical import of VEGF signaling remains unclear.…”
Section: Discussionsupporting
confidence: 57%
“…Nonetheless, increased expression of several pro-angiogenic growth factors have been found in human CCM lesions, including VEGF, PDGF, and TGF-β (Abe et al, 2009, Jung et al, 2003, Maiuri et al, 2006, Yildirim et al, 2010), and increased VEGF expression has also been measured in KRIT1 deficient animals (Corr et al, 2012). DiStefano et al showed that loss of KRIT1 increases VEGF expression by increasing nuclear β-catenin (DiStefano et al, 2014), where β-catenin stimulates transcription of VEGF (Glading and Ginsberg, 2010).…”
Section: Role Of Angiogenesis In Ccm Pathogenesismentioning
confidence: 99%
“…It is known that CM may be induced by radiation therapy or radiosurgery11,20), whereas de novo formations of CM without previous radiotherapy are rare1,2,3,5,8). Recent studies have demonstrated that the endothelial proliferation induced by VEGF may also contribute to de novo formation of CM1,5). It is possible that CM developed de novo in the present case, however, we could not definitively confirm that hypothesis because the previous MRI had been performed on a 1.5 tesla device.…”
Section: Discussionmentioning
confidence: 99%